BRIDGING THE CONVENTIONAL AND MOLECULAR METHODS FOR IDENTIFICATION OF RESISTANCE AGAINST FUSARIUM WILT IN CHICKPEA GERMPLASM - T. Shaheen1; S. Kausar; H. Ali; Mahmood-ur-Rahman1; T. Mahmud (Journal of Animal and Plant Sciences, 2017)
Chickpea is an economically important food crop and its production is affected by many biotic and abiotic factors. One of the common pathogens among root rot and wilt is Fusarium in chickpea producing regions of the world which causes yield loss upto 10% to 40%. In this study twenty eight chickpea genotypes were analysed for resistance against Fusarium caused by Fusarium oxysporum f.sp. ciceris wilt using both conventional and molecular methods to identify source of resistance. In conventional method, 28 chickpea germplasm lines were tested for effect of Fusarium oxysporum (Foc) belonging to race 2 in a completely randomized pattern. After about four weeks of inoculation the resistance and susceptibility of plants to Foc was obvious. In molecular analyses all twenty eight genotypes were screened with primers TA110, Tr19, Ts82, TA194, TA27 and TA96 and CS27A which are closely linked markers with Foc 2 resistance gene (Accession No. FJ538241). In eighteen of the genotypes the results of conventional study was found in accordance with molecular analysis. Marker assisted selection may be helpful in screening of available chickpea genotypes for wilt resistant genes. Chickpea genotypes identified as resistant during this study may be exploited in breeding programs to develop Foc race 2 resistant germplasm.
Keywords: Chickpea; Fusarium wilt; resistant genes; breeding